Estado da questão dos artigos em enfermagem e representações sociais no Brasil (2011-2016): possíveis contribuições para formação do enfermeiro - Pereira, Valclei Aparecida Gandolpho (2018)
Care as the guiding axis of Nursing provides much of the symbolization on the profession and guides the actions of teachers in undergraduate courses. The necessary understanding of caring phenomena leads Nursing research to the heterogeneity of theoretical approaches. The present study opted to approach the researches that seek in the Theory of Social Representations a theoretical-methodological instrument that makes possible understand symbolizations of the care, in order to contribute to the problematization of the nurse's training. The research had a double objective: (I) to identify and analyze the State of the Question of Nursing articles that adopted the Theory of Social Representations and (II) to understand the possible contribution of these studies to the nurse's training. After different investees to map the scenario, the following databases were elected in order to select the articles: Base de dados em Enfermagem, Literatura Latino-americana e do Caribe em Ciências da Saúde, Coleção Nacional das Fontes de Informação do SUS, Scientific Electronic Library Online, Medical Literature Analysis and Retrieval System Online, Bibliografia Brasileira de Homeopatia, Index Psi Divulgação Científica, Index Psi Psicologia, RIPSA Bibliografia em Indicadores da Saúde. In the temporal limit of five years (2011, 2012, 2013, 2014, 2015), 48 articles were selected in the simultaneous search for the keywords "nursing" and "social representations", and "nursing" and "social representation". Inclusion criteria were: documents in Portuguese described and set in Brazilian culture and society; directed and performed by nurses, focused on Nursing. Three corpora took place: (I) corpus composed by the introduction of the articles; (II) corpus composed by the articles section dedicated to the description of the methodology; (III) corpus composed by the sections of the articles referring to the results/considerations. The three corpora were processed separately in the computational lexical analysis program Alceste. From the consideration of the reports generated by the program, it can be seen that the articles studied presented the social representations as a provider of meaning to the service practices, capable to support the understanding of human relations, characterizing the Theory of Social Representations as a valuable tool for nurse’s training.